Calculation Method of Green Open Space Based on Carbon Emission from Transportation Sector in Surabaya - Ikhlas, Nurani; Abdullah, Taufik; Boedisantoso, Rachmat (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2017)
Surabaya is one of the metropolitan cities with dense transportation activities. Transportation is an activity contributes in increasing excessive release of carbon emmisions into the air. The increasing of carbon emmision can causes inventory green open space should be adjusted to reduce air pollution. The purpose of this study is to determine the green open space necessary based on the carbon emissions that is produced in the city of Surabaya. This study was conducted by the method of approach in Surabaya in each area of the transportation sector. The results show that the total green open space is needed in Surabaya is 66.526 km2 with total emission is produced 329,443.66 CO2/month or about 3,953,323.92 CO2/year.